Parental Bonding Dengan Perilaku Seksual Pada Remaja Berpacaran di SMKS Persatuan 1 Tulangan Sidoarjo - Wenny Ayu Larasati; Euvanggelia Dwilda F.S; Nining Febriyana (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
An attachment that exists between parents and children which forms the basis for the formation of an emotional relationship between the two so that it is one of the driving factors for adolescent sexual behavior. Parental involvement greatly influences risky or non-risky sexual behavior in adolescents, especially teenagers dating. The purpose of this study was to analyze the relationship between parental bonding and sexual behavior in adolescent dating. This type of research is quantitative with an observational analytical research design using a cross sectional approach. This study has a sample of 145 respondents or students according to the inclusion and exclusion criteria. Sampling was done by purposive sampling technique. Data collection in this study used a closed questionnaire via google form. Based on the results of the analysis of the Spearman's Rho correlation test, the correlation coefficient value is -0.265 with a p value of 0.017 (p <0.05) so it can be concluded that there is a relationship between parental bonding and sexual behavior in adolescent dating at SMKS Unity 1 Tulangan Sidoarjo with a negative relationship direction. which means that the quality of parental bonding given by parents to their children, then the involvement of children in risky sexual behavior will be less. Parents are expected to improve the quality of parental bonding with their children to prevent risky sexual behavior in adolescents Keywords: Parental bonding, sexual behavior, teenagers